Blind to what's in front of them: Theatre of the Oppressed and teacher reflexive practice, embodying culturally relevant pedagogy with pre-service teachers. Issue 1 (2nd January 2018) - Duffy, Peter; Powers, Beth
ABSTRACT: This study explores how using Theatre of the Oppressed (TO) techniques in combination with training on culturally responsive pedagogies (CRP) impacts pre-service teachers' perceptions of both themselves as future teachers and of the students whom they will teach. Classrooms in the United States and other parts of the world are undergoing dramatic demographic shifts. Research suggests that, in some US cities, the numbers of non-English speakers in classrooms is greater than native English speakers; 2015 marks the first year that non-White five-year-old children surpassed the number of White five-year-old children. The Pew Research Center and others have reported that 2020 will be the beginning of the "minority majority" in the US population. Demographic shifts; growing awareness of violence inspired by racism, cultural, linguistic, and ethnic diversity; expanded notions of identities and economic and social justice are discourses eschewed by many in privilege. Since the majority of teachers and pre-service teachers are White, it can be a challenge to substantively discuss CRP within contemporary classrooms. This study demonstrates how TO can play an important role in providing pre-service teachers with embodied experiences to understand CRP and encounter "the other."